THE EFFECTIVENESS OF PREVIEWING AS PRE-READING ACTIVITY TO IMPROVE STUDENTS' READINGCOMPREHENSIONAN EXPERIMENTAL STUDY ON THE SECOND GRADE STUDENTS OF SMPN 12 BANDUNG - Reni Nur Maryati, - (2008)
This research study entitled "The Effectiveness of Previewing as Pre-Reading Activity to Improve Students' Reading Comprehension (An Experimental Study at SMPN 12 Bandung)". It was aimed to investigate the effectiveness of previewing as pre-reading activity in improving students' reading comprehension and identifying the significant difference between the group that used previewing as pre-reading activity and the group that did not. The subjects of this study were second grade students of SMPN 12 Bandung. They were divided into two groups, experimental and control group, which consist of 40 students for each group. Both groups took pretest and posttest, whereas the treatment was only given to the experimental group. In relating to the purpose of the study, this study employed a quasi experimental study which involved administering two kinds of instruments, reading comprehension and questionnaire. The reading comprehension test was used to investigate students' reading comprehension ability before and after treatment and the questionnaire was used to investigate the students' response towards previewing. Based on the calculation of the data, it was demonstrated that after the treatment there was a significant difference on students reading comprehension between experimental and control group (t = 6.047, p = 0.000). The results of the study also showed that there was a significant difference on the experimental group's pretest and posttest scores (t = -8.031, p = 0.000). Furthermore, the results showed that there was no significant difference on the control group's pretest and posttest scores (t = 1.718, p = 0.094). Moreover, the results of the questionnaire showed that most of the students preferred to use previewing in their reading activity. Statistically, the result of the study proved that there was a significant difference between the experimental group that used previewing and the control group that did not. This also led to the conclusion that the previewing is effective in improving students' reading comprehension.